Improving Students’ Speaking Skill Through Questioning Paper at Kampung Inggris Pare - Kadnawi, M.Pd (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2021)
Speaking plays an important role in language learning, so the students should master the speaking skill in order to answer the questions appropriately and efficiently. In this case teachers have to help students change their inefficient speaking habits (speaking word by word, focusing too much attention on form, and relying heavily on dictionary), by teaching them efficient speaking skills. A guided speaking is an effective way to do this; in this way the students can learn how to speak in different purposes and situation. Questioning paper is written question on paper that has purpose for self-practice everywhere. It is an alternative way to improve their speaking skill. Questioning paper technique is the activities of students to guess and make conversation by using some questions provided. It can help and stimulate the students to make conversation. The researcher uses Classroom Action Research (CAR) as the approach of the research. Classroom Action Research (CAR) is systematic inquiry with the goal of informing practice in a particular situation. CAR is a way for instructors to discover what works best in their own classroom situation, thus allowing informed decisions about teaching. This classroom action research (CAR) was conducted in two cycles in which each cycle covered four stages of activities. They were as follows: (1) the planning of the action (2) implementing (3) class observing (4) reflecting on the action. In this research, the researcher finds the significant improvements in the first and second cycles. Furthermore, the researcher administered post test to measure the improvement of speaking skill by using questioning paper. The researcher has found the significant results that is 95 % of students earning above. Keywords: Speaking skill, Questioning paper